Is it useful to stimulate roots in the diagnosis of cervical root compression? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Electrophysiology can be very important in diagnosing root pathologies, but the classic electrophysiologic methods lack an objective measurement tool. In this study, diagnostic validity of cervical spinal root stimulation (CRS) was evaluated in patients with suspected cervical radiculopathy. CRS, converttional needle electromyography, and magnetic resonance imaging were performed in 14 patients. The control group included 10 healthy individuals. A monopolar needle electrode was used for the CRS. Compound muscle action potentials were recorded from biceps, triceps, and abductor digiti minimi muscles. Thirty root pairs in the control group and 40 root pairs in the patient group were stimulated. Latencies and amplitudes of the compound muscle action potentials were found abnormal in 5 (35.7%) and 10 (71.4%) patients, respectively. Electromyographic findings of root compression were seen in 10 patients (71.4%). The CRS results were positive in 7 out of 10 patients with positive electromyography findings of root dysfunction. Our results suggest that CRS may be a complementary diagnostic tool. Technical difficulties and lack of reference data make its use difficult as a routine electrophysiologic test for diagnosing nerve root dysfunction.
Keywords: radiculopathy; cervical root stimulation; electromyography; SPINAL NERVE-STIMULATION; H-REFLEX; RADICULOPATHY; ELECTROMYOGRAPHY